P024 Disturbed sexual functioning in female patients with idiopathic inflammatory myopathies. (March 2019) - Hermankova, B; Spiritovic, M; Smucrova, H; Oreska, S; Storkanova, H; Pavelka, K; Senolt, L; Mann, H; Vencovsky, J; Tomcik, M
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Idiopathic inflammatory myopathies (IIM) are characterized by inflammation and atrophy of skeletal muscles, pulmonary and articular involvement, which leads to functional impairment, reduced quality of life including sexual life. Objectives: The aim of this study was to assess sexual functions/quality of life and pelvic floor function in female IIM patients compared to age-/sex-matched healthy controls (HC). Methods: In total, 22 women with IIM [mean age: 55.1, disease duration: 7.9 years, dermatomyositis (DM, 8)/polymyositis (PM, 10)/necrotizing myopathy (IMNM, 3)/inclusion body myositis (IBM, 1)], who fulfilled the Bohan/Peter 1975 criteria for DM/PM, and 22 healthy controls (mean age: 55.1 years) filled in 12 well-established and validated questionnaires assessing sexual function and pelvic floor function, fatigue, physical activity and depression. We used the following questionnaires: Female Sexual Function Index (FSFI), Brief Index of Sexual Function for Women (BISF-W), Sexual Quality of Life Questionnaire (SQoL-F), Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12), Pelvic Floor Distress Inventory Questionnaire (PFIQ7), Fatigue Impact Scale (FIS), Beck's Depression Inventory II (BDI II), Health Assessment Questionnaire (HAQ) and Human Activity Profile (HAP). Results: Compared to HC, patients with IIM had significantly higher prevalence and greater severity of sexual dysfunction (FSFI, BISF-W: in all subscales as well as total scores), dysfunction of pelvic floor (PISQ-12), and worse sexual quality of life (SQoL-F). Worse scores in IIM patients were associated with elevated muscle enzyme levels [lactate dehydrogenase: FSFI (r=−0.524, p=0.0123), BISFW (r=−0.528, p=0.0115)], greater fatigue [FIS: FSFI (r=−0.434, p=0.0438), BISF-W (r=−0.488, p=0.0211), SQoL-F (r=−0.488, p=0.0070), PISQ-12 (r=0.643, p=0.0013)], more severe depression [BDI-II: PISQ-12 (r=0.474, p=0, 0258)], deteriorated quality of life [HAQ: PISQ-12 (r=0.476, p=0.0252)], and worse ability to perform physical activities [HAP: FSFI (r=0.437, p=0.0417), BISF-W (r=0.451, p=0.0351), PISQ-12 (r=−0.494, p=0.0195)]. Conclusions: Women with IIM reported significantly disturbed sexual function, sexual quality of life and pelvic floor function than age-matched healthy controls. Worse scores in IIM were associated with disease activity, physical activity, fatigue, depression and quality of life. Acknowledgements: Supported by AZV-16-33574A, MHCR 023728, and SVV – 2 60 373. Disclosure of Interest: None declared.